G37(P) Incidence of NEC before and after the introduction of probiotics. (27th April 2016) - Gaskell, R; Ross, S; Odd, D; Mann, R; Griew, P; Matthews, J; Bartle, D
Abstract : Introduction: Enteral probiotics have been shown to reduce the incidence of severe necrotising enterocolitis (NEC) and mortality in premature infants under 1500g. 1 A 2014 Cochrane review strongly suggested a change in practice and recommended comparative studies of preparations, timing and treatment length. Incidence of NEC was substantially reduced in a prospective cohort study in a North American NICU after introduction of probiotics [2]. We were interested to assess the impact on NEC, sepsis and death after probiotics had been introduced in several units in the southwest of England. Methods: We administered a probiotic containing Bifidobactum and Lactobacillus, to all patients less than 32 weeks or under 1500g since July 2013. Using Badgernet (a database for all admitted babies in the United Kingdom) we looked at incidence of NEC, sepsis, death and length of stay, before the introduction of probiotics in 2011 and compared this with the incidence after the introduction in 2014. NEC was defined as any baby having confirmed or suspected NEC as a diagnosis on Badgernet and was applied only to inborn babies. We then compared the data of the 3 units that had introduced probiotics, with data from 3 similar units in the network, that hadn't. Results: In the units using probiotics, suspected or confirmed cases of NEC were reduced from 25/169 admissions (15%) to 18/174 admissions (10%). Cases of NEC or death were reduced from 34/169 (20%) to 23/174 (13%). Average length of stay was unchanged at 38 days. In those units that hadn't started probiotics, suspected or confirmed NEC slightly increased in 2014. The odds ratio (odds of NEC on probiotics/ odds of NEC not on probiotics) = 0.64. This suggests a reduction in risk from using probiotics, however, the confidence limits are wide (95% CLs are 0.34, 1.16) and thus this is not statistically significant. Conclusion: There would appear to be a trend towards reduction of NEC in units since the introduction of probiotics however this is not statistically significant. We recognise the results are limited by the data being input. As probiotics are introduced into more units, prospective data collection is needed in order to look for a significant reduction in individual units.